Optimalisasi Kualitas Produk Air Mineral Cup dengan Pendekatan Metode Seven Tools dan New Seven Tools di CV. Tirta Sasmita - Tedi Dahniar; Fredy Dwi Ibnu Saputra (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2023)
Water is one of the needs of human life which is very important for the body. The great need for water is read by companies to produce bottled drinking water. Bottled Drinking Water (AMDK) is drinking water that is ready to be consumed directly without prior heating. CV. Tirta Sasmita is a company at Pamulang University that only makes bottled water, CV. Tirta Sasmita understands that there is an opportunity to make a profitable business. In fact, in the production process, there are still many reject products, especially 220 ml glass cup products. The purpose of this research is to reduce product rejects by using a combination of Old Seven tools and New Seven tools by controlling the level of product damage in the company. After repairs were made to the factors that caused the Defect Cup Leaking problem, it managed to drop from 1991 to 546 pcs, or a decrease of 72.60%. Thus the improvement activities carried out succeeded in solving the problems that occurred in the production process of 220 ml Cup bottled water.